2021
DOI: 10.3390/nu13124373
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Week Randomized Double-Blind Placebo-Controlled Clinical Trial, Evaluating the Effect of Supplementation with a Spinach Extract on Skeletal Muscle Fitness in Adults Older Than 50 Years of Age

Abstract: The aim of a 12-week randomized double-blind placebo-controlled study was to assess the effect of daily supplementation with a natural extract of Spinacia oleracea L. (4 × 500 mg capsules/day; total 2 g per day) combined with a moderate-intensity training program (1 h session/3 times a week) on skeletal muscle fitness in adults over 50 years of age. Muscle strength assessed by isokinetic and isometric dynamometry improved significantly in the experimental (n = 23) and the placebo (n = 22) groups, but the magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…[26] Similarly to the results in young men, a recently published study reports an increase of skeletal muscle fitness after spinach extract administration for 12 weeks in adults over 50 years of age. [18] In previous studies, the urinary elimination and metabolism of ecdysterone were reported following the administration of ecdysterone supplements or pure ecdysterone to humans. [27][28][29][30] Concerning an application in doping control analysis, the urinary elimination and metabolism of ecdysterone were reported following the administration of ecdysterone supplements or pure ecdysterone in humans.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[26] Similarly to the results in young men, a recently published study reports an increase of skeletal muscle fitness after spinach extract administration for 12 weeks in adults over 50 years of age. [18] In previous studies, the urinary elimination and metabolism of ecdysterone were reported following the administration of ecdysterone supplements or pure ecdysterone to humans. [27][28][29][30] Concerning an application in doping control analysis, the urinary elimination and metabolism of ecdysterone were reported following the administration of ecdysterone supplements or pure ecdysterone in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Ecdysteroids have long been recognized for various potential beneficial effects on animal species and humans, including hypolipidemic, antidiabetic, hepatoprotective, adaptogenic as well as growth-promoting and anabolic effects. [12][13][14][15][16][17][18][19][20][21] In vivo and in vitro studies have shown that ecdysterone increases protein synthesis and muscle mass. [20,21] As reported in Parr et al, [21] this effect involves mediation by estrogen receptor beta (ER-𝛽).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, (S)-2A2HB was not available commercially, but the presumed deacetylated metabolite (S)-2HB was viewed as a possible mechanism-based HDAC inhibitor, analogous to sulforaphane metabolites [8,34]. Using molecular docking in silico, favorable interactions were predicted for (S)-2A2HB, (S)-2HB and the enantiomeric metabolite (R)-2HB with allosteric sites in HDAC1-and HDAC3-containing corepressor complexes (Figure 5C).…”
Section: Discussionmentioning
confidence: 99%
“…Recent human clinical intervention trials have assessed diverse aspects of SPI intake, including anthropometric measures, muscle fitness, metabolic profiles, arterial stiffness, and urinary biomarkers [5,[34][35][36], extending prior research on the health benefits of green leafy vegetables and the functional properties of spinach-derived phytochemicals and bioactives [37][38][39][40][41]. We reported that long-term feeding of freeze-dried SPI at 10% w/w in the diet for 26 weeks exhibited significant antitumor efficacy in the Pirc model, resulting in >60% reduced tumor multiplicity in the colon and small intestine [6].…”
Section: Discussionmentioning
confidence: 99%